Character, goals and progress of the common agricultural policy of the European Union - Dimitrov, Slavi Petrov (UFPR, 2006)
Agricultural sector is among the most important, mostdebatable and most financed activities in the European Union.The complicated relations in the Union require coordinatedcommon policy, known as Common agricultural policy of theEuropean Union. Such policy enables the most efficient useof resources and supporting the countries which are about tojoin the Union.